2011
DOI: 10.4162/nrp.2011.5.6.548
|View full text |Cite
|
Sign up to set email alerts
|

The estimated daily manganese intake of Korean children aged 11-12

Abstract: The purpose of this study was to estimate the daily manganese (Mn) intake of Korean children. This study was done using a three-day dietary intake survey of 257 Korean children (boys 123; girls 134). The Mn intake values were calculated based on a database that provides the Mn content of the frequently consumed Korean foods, alongside the food composition table provided by the Korean National Rural Living Science Institute. The average age, height, weight and body mass index of our subjects were 11.9 years, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…In one study conducted in Korea, intake of Mn by 257 children between the age of 11 and 12 was 4.6 mg for boys and 4.0 mg for girls, which were similar findings to the results of this research [17]. In one study conducted in Korea, intake of Mn by 257 children between the age of 11 and 12 was 4.6 mg for boys and 4.0 mg for girls, which were similar findings to the results of this research [17].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In one study conducted in Korea, intake of Mn by 257 children between the age of 11 and 12 was 4.6 mg for boys and 4.0 mg for girls, which were similar findings to the results of this research [17]. In one study conducted in Korea, intake of Mn by 257 children between the age of 11 and 12 was 4.6 mg for boys and 4.0 mg for girls, which were similar findings to the results of this research [17].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, it was found that the average daily energy intake in elementary schoolchildren aged 6-11 was 1,807.2 kcal, which was slightly higher than the energy intake of the relevant age group in the KNHANES and was lower than that of children between the age of 12 and 18. And based on a previous study [17] which was conducted on 257 Korean children that showed 2,142 kcal for daily energy intake, the daily energy intake of the subjects of this study was similar. In addition, a food consumption survey was performed according to the 24-hour food record method in this study.…”
Section: Discussionmentioning
confidence: 59%
“…In the current study, cereals, vegetables, beans and fruit were the main food sources of dietary Mn, which were consistent with previous studies. It has been suggested that cereals, vegetables and beans are the major food groups contributing to dietary Mn in Korean children [49], and more than 42% of dietary Mn was reported from rice in south China [44]. Although refined grains were positively associated with type 2 diabetes, the potential protective effect of food groups rich in Mn has been documented [50].…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Magnesium deficiency appears to increase the production of free radicals and the sensitivity of cells to the attack of reactive oxygen species. 53,54 Hypomagnesemia favors the infiltration of neutrophils and macrophages in the affected cells, which potentiates the activity of the enzyme nicotinamide adenine dinucleotide phosphate oxidase (NADPH oxidase), increasing the production of the superoxide radical. 46,55 Hypomagnesemia also contributes to reduce the expression and activity of antioxidant enzymes, such as glutathione peroxidase (GPx), superoxide dismutase (SOD) and catalase (CAT), and cellular and tissue antioxidant concentrations, as well as increases the production of hydrogen peroxide by inflammatory cells.…”
Section: Metabolic and Physiological Aspects Of Magnesiummentioning
confidence: 99%